Hubungan Religiositas Dengan Prilaku Prososial Di Lingkungan Semester V Fakultas Dakwah Dan Komunikasi UINSU - Alya Azra Mutia Nasution; Zidan Syahira; Jacky Raihanta Barus; Ahmad Sakban Wahyudi (CV. ITTC INDONESIA, 2024)
In general, positive activities tend to build healthy communities and social relationships, while negative activities tend to damage and divide communities. Both affect the social dynamics of a group or society. Religiosity is the level of an individual's commitment to the religion he adheres to and its teachings, which is shown by attitudes and behaviors that are consistent with this commitment. Religiosity can be understood that religion is not only vertical in the sense that it only regulates human relationships with God or is limited to mahda worship rituals. However, religion is also horizontal, namely religion teaches its followers how to relate to fellow humans and also the surrounding nature.